Auditor Tenure and the Ability to Meet or Beat Earnings Forecasts* - Davis, Larry R.; Soo, Billy S.; Trompeter, Gregory M. (Contemporary Accounting Research, 2009)
We examine the relation between auditor tenure and a firm's ability to use discretionary accruals to meet or beat analysts' earnings forecasts. We find evidence over the period 1988-2006 that firms with both short and long tenure are more likely to report levels of discretionary accruals that allow them to meet or beat earnings forecasts. These results suggest that while regulatory mandates for periodic auditor turnover have negative effects, sustained long-term auditor-client relationships may also be detrimental to audit quality. Further, although we observe a positive relation between tenure and the use of discretionary accruals to meet or beat earnings in the pre-Sarbanes-Oxley (SOX) period, we do not observe such a relation in the post-SOX period. This latter finding is consistent with regulatory reforms and heightened scrutiny of financial reporting in the post-SOX period resulting in less aggressive efforts at managing earnings by client firms and/or increased diligence on the part of auditors. These findings may not generalize to firms that are not covered by analysts, because these firms do not face the same public pressure to manage earnings in order to meet or beat expectations. © CAAA.